Exosomal miR-205-5p enhances angiogenesis and nasopharyngeal carcinoma metastasis by targeting desmocollin-2 - Wenjuan Yang; Shiming Tan; Lixia Yang; Xiaohui Chen; Ruiqian Yang; Linda Oyang; Jinguan Lin; Longzheng Xia; Nayiyuan Wu; Yaqian Han; Yanyan Tang; Min Su; et al. (Molecular Therapy: Oncolytics, 2022)
The aim of this study was to investigate whether and how exosomal miR-205-5p regulated angiogenesis and nasopharyngeal carcinoma (NPC) metastasis. We found that up-regulated serum exosomal miR-205-5p levels were associated with NPC progression and worse overall survival of NPC patients. miR-205-5p over-expression significantly increased tube formation, wound healing, migration and invasion of NPC cells, and lung metastasis of NPC tumors, whereas miR-205-5p inhibition had opposite effects. Exosomal miR-205-5p from NPC cells promoted the migration, tube formation, and microvessel density (MVD) of HUVECs in vitro and in vivo. Furthermore, bioinformatics-, luciferase reporter-, and biotinylated miR-205-5p-based pull-down assays indicated that miR-205-5p directly bound to the 3′ UTR of desmocollin-2 (DSC2). Exosomal miR-205-5p targeted DSC2 to enhance the EGFR/ERK signaling and MMP2/MMP9 expression, promoting angiogenesis and NPC metastasis, which was abrogated by DSC2 over-expression. Finally, the levels of miR-205-5p transcripts were positively correlated with MVD but negatively with DSC2 expression in NPC tissues, and patients with miR-205high/DSC2low NPC had worse overall survival. In conclusion, exosomal miR-205-5p promotes angiogenesis and NPC metastasis by targeting DSC2 to enhance EGFR/ERK signaling and MMP expression. This exosomal/miR-205-5p/EGFR/ERK axis may be a new therapeutic target for intervention of NPC metastasis.